Cell-Type-Specific Tyrosine Phosphorylation of the Herpes Simplex Virus Tegument Protein VP11/12 Encoded by Gene UL46 - Zahariadis, George (American Society for Microbiology (ASM), 2008)
Cytotoxic T lymphocytes (CTL) and natural killer (NK) cells play key roles in limiting herpesvirus infections; consequently, many herpesviruses, including herpes simplex virus (HSV), have evolved diverse strategies to evade and/or disarm these killer lymphocytes. Previous studies have shown that CTL and NK cells are functionally inactivated following contact with HSV-infected fibroblasts. During studies of the mechanisms involved, we discovered that HSV-inactivated NK-92 NK cells and Jurkat T cells contain a strikingly prominent, novel, ca. 90-kDa tyrosine-phosphorylated protein that we identified as the HSV tegument protein VP11/12. Inasmuch as VP11/12 produced in fibroblasts and epithelial cells is not obviously tyrosine phosphorylated, these data suggested that VP11/12 serves as the substrate of a cell-type-specific protein tyrosine kinase. Consistent with this hypothesis, VP11/12 was also tyrosine phosphorylated in B lymphocytes, and this modification was severely reduced in Jurkat T cells lacking the lymphocyte-specific Src family kinase Lck. These findings demonstrate that HSV tegument proteins can be differentially modified depending on the cell type infected. Our data also raise the possibility that VP11/12 may modulate one or more lymphocyte-specific signaling pathways or serve another lymphocyte-specific function. However, HSV type 1 mutants lacking the UL46 gene retained the ability to block signaling through the T-cell receptor in Jurkat cells and remained competent to functionally inactivate the NK-92 NK cell line, indicating that VP11/12 is not essential for lymphocyte inactivation. Further studies are therefore required to determine the biological function of tyrosine-phosphorylated VP11/12.